Fitnah Politik Dalam Perspektif Hadist Dan Pasal 27A UU 1/2024 - Ghazyan Hidzyam Haqqani; Tajul Arifin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Political slander has become a significant challenge in modern political life, affecting social and political stability and triggering detrimental conflicts.This article investigates the perspectives of the hadith narrated by Muslim No. Hadith: 1855 and Article 27A of Law No. 1/2024 regarding political slander. The hadith under scores the importance of having honest leaders committed to the common good, while modern regulations attempt to address slander through the enforcement of honesty and transparency in politics. This article also discusses the impacts of slander, prevention efforts, the role of governments, and the implementation of Islamic values in positive law. In conclusion, integrating moral teachings with legal regulations can help create afairer and more moral political system, safe guarding public interests and promoting social stability.